Twenty-first-century shapes of the Church? - Williams, John (Theology, 2011)
Recent years have seen a burgeoning of literature addressing the future prospects of the churches. This article analyses this material into six broad approaches, representing a range of church responses to a socio-cultural diagnosis the author terms ‘popular postmodernity’. The author argues that the churches’ adoption of this diagnosis is sociologically unsophisticated in a similar way to their earlier handling of the ‘secularization’ thesis. He cites examples from the literature to propose that the churches need to engage more critically with questions of socio-cultural analysis, ecclesiology and the status of orthodoxy in developing their new strategies for mission and ministry.